Teacher Mindfulness and Classroom Management: How Awareness Shapes the Use of Reinforcement and Punishment in Education - Najmi Hayati (JINoP (Jurnal Inovasi Pembelajaran), 2025)
This study investigates the impact of teacher mindfulness on classroom management, focusing on how awareness influences the application of reinforcement and punishment strategies. The aim is to determine whether mindfulness practices improve teachers' use of behavioral interventions in educational settings. The study involved 29 teacher participants in Madrasah Aliyah Ittihadul Muslimin of Province Riau in July 2024, all engaged in a structured mindfulness training program. A mixed-methods approach was utilized. The quantitative phase employed a pre-test–post-test design to measure changes in classroom management practices and mindfulness levels. The qualitative phase included reflective journaling and semi-structured interviews to gain insight into teachers' experiences with mindfulness and behavior management. Quantitative results indicated a significant increase in the use of positive reinforcement and a reduction in punitive strategies following the intervention. The most significant gains were observed in Acting with Awareness (mean increase of 3.59) and Observing (mean increase of 2.72), critical to intentional and reflective classroom behavior management. Qualitative analysis revealed themes of improved emotional regulation, increased awareness, and more thoughtful responses to student behavior. The findings suggest that mindfulness enhances teachers' capacity to manage classrooms effectively by encouraging more balanced and intentional use of reinforcement and punishment.